Do-it-yourself patents. - Loebner, H.
This paper provides some important advice on how you can write and apply for your own patent without the help of a lawyer. Some of the useful advice given include conducting extensive patent searches via the Internet, purchasing software for correctly constructing and formatting patents, and filing an appeal when the examiner rejects your patent.
Keywords: Internet searches; US Patent Office; Patent appeals; Patent application; Patent formatting